Degradable magnesium implant-associated infections by bacterial biofilms induce robust localized and systemic inflammatory reactions in a mouse model. (13th September 2017) - Rahim, Muhammad Imran; Babbar, Anshu; Lienenklaus, Stefan; Pils, Marina C; Rohde, Manfred
Abstract: Biomaterial-associated Pseudomonas aeruginosa biofilm infections constitute a cascade of host immune reactions ultimately leading to implant failure. Due to the lack of relevant in vivo biofilm models, the majority of the studies report host immune responses to free-living or planktonic bacteria, while bacteria in clinical situations live more frequently as biofilm communities than as single cells. The present study investigated host immune responses to biomaterial-associated P. aeruginosa biofilms in a clinically relevant mouse model. Previously, we reported metallic magnesium, a prospective biodegradable implant, to be permissive for bacterial biofilm in vivo even though it exhibits antibacterial properties in vitro . Therefore, magnesium was employed as biomaterial to investigate in vivo biofilm formation and associated host immune responses by using two P. aeruginosa strains and two mouse strains. P. aeruginosa formed biofilm on subcutaneously implanted magnesium disks. Non-invasive in vivo imaging indicated transient inflammatory responses at control sites, whereas robust prolonged interferon- β (IFN- β ) expression was observed from biofilm in a transgenic animal reporter. Furthermore, immunohistology and electron microscopic results showed that bacterial biofilms were located in 2D immediately on the implant surface and at a short distance in the adjacent tissue. These biofilms were surrounded by inflammatory cells (mainly polymorphonuclear cells) compared to the controls. Interestingly, even though the number of live bacteria in various organs remained below detectable levels, splenomegaly indicated systemic inflammatory processes. Overall, these findings confirmed the resistance of biofilm infections in vivo to potentially antibacterial properties of magnesium degradation products. In vivo imaging and histology indicated the induction of both local and systemic host inflammatory responses to P. aeruginosa biofilms. Even though the innate host immune defenses could not eliminate the local infection for up to two weeks, there was no apparent systemic bacteremia and all the animals investigated survived the infection.